2019
DOI: 10.5435/jaaos-d-18-00658
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Opioid Use Negatively Affects Patient-reported Outcomes After Primary Total Hip Arthroplasty

Abstract: Background: Opioid use is a public health crisis in the United States and an area of increased focus in orthopaedic surgery. The aim of this study is to investigate whether preoperative opioid use had any effect on patient-reported outcome measures (PROMs) before and after total hip arthroplasty (THA). Methods: A total of 389 patients with THA with both preoperative and postoperative PROMs were reviewed: (1) 76 patients with preoperative opioid use (24%) and (2) 237 patients without preoperative opioid use (76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…4,6,7,20,56,59 Similar studies have also identified preoperative opioid use as a negative predictor of patient-reported outcome measure scores, with lower preoperative baseline scores and lower overall change in function after arthroplasty. 12,31,32,33,50 A similar relationship has been found in patients undergoing RCR. 45,58 However, there is a paucity of data regarding the relationship between preoperative opioid use and postoperative complications, health care utilization, and need for revision surgery after RCR.…”
supporting
confidence: 75%
“…4,6,7,20,56,59 Similar studies have also identified preoperative opioid use as a negative predictor of patient-reported outcome measure scores, with lower preoperative baseline scores and lower overall change in function after arthroplasty. 12,31,32,33,50 A similar relationship has been found in patients undergoing RCR. 45,58 However, there is a paucity of data regarding the relationship between preoperative opioid use and postoperative complications, health care utilization, and need for revision surgery after RCR.…”
supporting
confidence: 75%
“…In addition, the use of preoperative opioids among orthopedic patients has been reported to cause poor clinical outcomes and increase the risk of reoperation. 30 31 We also found that among the current opioid users within three months after fracture, patients with a history of opioid use within six months prior to the fracture had a higher risk of sustained opioid use. This finding is in agreement with the results of a study that reported that preoperative opioid experience could increase the likelihood of opioid abuse.…”
Section: Discussionmentioning
confidence: 66%
“…The results from this study support the growing evidence that preoperative opioid use is associated with worse surgical outcomes compared to nonusers. [6,10,18,20,[32][33][34][35] Using a propensity score matched analysis of SASD patients enrolled into a prospective, multi-center study, we found that SASD patients using opioids preoperatively 1) reported worse preoperative quality of life including greater pain, worse physical function and mental health, and worse selfimage, despite having similar medical comorbidities, and similar magnitudes of spine deformities as preoperative nonusers; 2) demonstrated longer ICU stay and longer hospital stay, despite having similar surgery performed as preoperative opioid nonusers; 3) had worse quality of life following surgery including greater residual pain, worse function, worse self-image, and were less satisfied with surgical treatment, despite having similar surgeries and similar complication rates as preoperative opioid nonusers; 4) had greater hospital costs and worse postoperative cost/QALY; and 5) had greater postoperative opioid use and had 4.7 times greater risk of continued opioid use at mean 3.3 years postoperative follow-up compared to nonusers. Little data exists regarding the impact of preoperative opioid use on outcomes for SASD.…”
Section: Discussionmentioning
confidence: 99%